Implementasi Pembelajaran Kitab Targhib Wa Tarhib pada Bab Sholat di Kelas I’dad C1 Sebagai Upaya Religiusitas Santri Pondok Pesantren Darun Najah Karangploso Malang - Wahyudi Yudi; Rindi Antika Diah Rohma (At Turots: Jurnal Pendidikan Islam, 2022)
Education is an important thing that must be carried out by everyone. Without education a person will not be able to progress and develop to fulfill all his life goals. In the process of education does not always have to go through formal institutions. Informal institutions can also be a business in education, the most important thing is that there is a goal that must be achieved in education in Indonesia, one of which is to instill religious characteristics, therefore researchers want to examine how to instill and improve religious characteristics to students through books. targhib wa targhib, to obtain the results of this study properly the researchers used qualitative research methods, as we know the book of targhib is one of the books to instill the religious nature of a student through the material contained in the book with the efforts of educators in instilling the contents of the material contained in the book. in the book such as through practice and drill is one way of transferring knowledge to students so that it is truly embedded in the knowledge students contained in the book of targhib wa targhib so as to improve the religious nature of students